2011
DOI: 10.1007/s10157-011-0414-4
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of calbindin D28k in the late distal tubules in the potassium-loaded adrenalectomized mouse kidney

Abstract: Upregulation of calbindin in the late distal tubule suggests that Ca(2+)-dependent K transport may function as an alternative mechanism for urinary K excretion in ADX mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The P[aldo] for Con mice of 239 pg/ml ( Table 1 ) using ELISA was close to the values of 322 pg/ml [ 17 ] and 400 pg/ml [ 34 ] of previous studies using radioimmunoassay (RIA). For HK diet, our value of 753 pg/ml using ELISA was less than the value of 1797 ± 630 using RIA [ 32 ]; however, the SEM of the RIA value indicates some readings in the range of our value.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The P[aldo] for Con mice of 239 pg/ml ( Table 1 ) using ELISA was close to the values of 322 pg/ml [ 17 ] and 400 pg/ml [ 34 ] of previous studies using radioimmunoassay (RIA). For HK diet, our value of 753 pg/ml using ELISA was less than the value of 1797 ± 630 using RIA [ 32 ]; however, the SEM of the RIA value indicates some readings in the range of our value.…”
Section: Discussionmentioning
confidence: 58%
“…Mice on LNaHK [ 9 ], or HK [ 8 , 32 , 33 ] exhibit a urinary flow that is 5-fold that of Con mice. A high urine volume is necessary to dilute the K in the CNT/CCD and excrete K at a high rate because the concentration of K that can be secreted in the CNT/CCD is limited to approximately 120 mM [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our data are in line with observations in humans with type 1 aldosterone deficiency, who are usually still able to adapt renal K + excretion and to stay more or less in K + balance. 38 Likewise, adrenalectomized animals 23,24,39 were shown to augment renal K + excretion in response to an increased dietary K + intake, although usually at the expense of more or less elevated plasma K + levels. Previous studies on adrenalectomized rats and rabbits indicated that a high-K + diet increases renal Na + and K + channel activities independent from aldosterone.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 However, adrenalectomy is not always complete and residual plasma aldosterone levels may persist. 24 Moreover, local aldosterone producing systems may exist in many organs including the kidney. 25 Hence, we used mice with targeted inactivation of the aldosterone synthase (AS) 26 to analyze in detail the cellular and molecular mechanisms involved in the regulation of K + homeostasis under conditions of complete aldosterone deficiency.…”
mentioning
confidence: 99%
“…Kidney sections were immuno-stained, as described previously [ 7 , 28 ]. In brief, the sections were blocked with 5% normal goat serum and reacted with rabbit polyclonal anti-human Epo antibody (sc-7956, 1:50; Santa Cruz Biotechnology, Santa Cruz, CA, USA), followed by Histofine Simple Stain MAX-PO (414341F; Nichirei Bioscience, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%